New PCSK9 inhibitor miR-552-3p reduces LDL-C via enhancing LDLR in high fat diet-fed mice. (May 2021) - Ma, Ningning; Fan, Lei; Dong, Yunxia; Xu, Xiaoding; Yu, Chuwei; Chen, Jing; Ren, Jin
Abstract: PCSK9 has emerged as a promising new therapeutic target for hyperlipidemia. The efficacy of PCSK9 siRNA in clinic trials clues the feasibility of exploring more PCSK9 inhibitors based on genetic inhibition in the treatment of hyperlipidemia. MicroRNAs (miRNAs) as a class of endogenous non-coding small RNAs can regulate genes at transcriptional and/or translational level. Here, we screened miRNAs from the prediction of TargetScan database with possible inhibitory activities in PCSK9 protein level via AlphaLISA and Western blotting, in which miR-552-3p was selected out for its strongest inhibitory effect. MiR-552-3p could bind to the 3' untranslated region (3'-UTR) of PCSK9 to inhibit translation and interact with the promoter of PCSK9 to suppress transcription. Further in vitro and in vivo experiments proved the effects of miR-552-3p on PCSK9 and downstream effectors: it could increase LDLR protein level, promote LDL-C uptake in HepG2 cells and lower serum LDL-C in high fat diet (HFD)-fed mice. In conclusion, our findings firstly identified miR-552-3p as a new PCSK9 inhibitor with the dual-inhibition mechanism, which suggested the possible application of miR-552-3p in the treatment of hyperlipidemia. Graphical Abstract: ga1